Development, production, and quality of peas under different soil water tension - Marouelli, Waldir Aparecido (1991)
To analyse several production components of dry pea under different soil water regimes, some field experiments were carried out at Centro Nacional de Pesquisa de Hortaliças, Brasília, DF, Brazil, in the years of 85, 86, and 87. Sixteen factorial treatments resulted from applying four levels of soil water tension (25, 50, 100, and 200 kPa) in two stages of plant growing. Best productivities were found at 200 kPa of soil water tension on vegetative and reproductive stages, as a result of the greater grain size and smaller stand reduction. Seed germination was not influenced by soil water status. On the other hand, decoloration and rehydration capacity of grains were reduced as soil water tension increased during the reproductive stage.